Co-developing and co-validating location-specific fertilizer and agroclimate advisory service for Wheat in Ethiopia: the Digital Green Use Case - Liben, Feyera M.; Ebrahim, Mohammed; Abera, Wuletawu; Erkossa, Teklu; Bogale, Beza; Kebede, Firew; Ayele, Mengistu; Alitaseb, Tesfu; Haji, Abdurahman; Tsegu, Abera; Girmaw, Mekdes; Ayele, Kebede; et al. (2022)
This report addresses activities conducted during the Incubation Phase of the Excellence in Agronomy (EiA) “Digital Green Ethiopia Use Case”. The report outlines the major activities implemented from proposal development to the execution of the main activities and associated results. The focus of the Use Case was to capitalize on the datasets and resources of the coalition of the willing (CoW) led by the Alliance of Bioversity and CIAT and supported by GIZ) to develop and pilot a minimum viable product (MRV) related to the development of an agroadvisory tool incorporating fertilizer, crop planting date and wheat rust surveillance for wheat value chain in Ethiopia. EiA is generally composed of content development and associated demand partner. In this case, the Alliance and its team envisaged developing location-specific agroadvisory (content) and Digital Green would disseminate the content to extension and farmers using its agile channels. Accordingly, the Alliance team in Ethiopia supported by EiA and CoW team developed an integrated location-specific fertilizer recommendation tool that has been validated on selected farmers. in three regions and four Woredas of Ethiopia. Close to 300 farmers participated in the trails which were composed of: national blanket recommendation, local optimal recommendation (based on local research institutes, Universities, etc.), and the data-driven location-specific recommendation developed by the CoW-EiA collaborative project. Note that the ‘local optimal’ recommendation relates to commonly applied fertilizer type and rate based on suggestion by local experiences (applied in the four sites) but with no adequate documentation. Also note that the data-driven location-specific fertilizer recommendation refers to one developed through the collaborative effort of the CoW (supported by Alliance, GIZ-Ethiopia and EiA), in general referred to as the ‘Digital Green Use Case (DGUC). While evaluating the three trials, the Farmers’ field days and data analysis results clearly showed that the DGUC has produced significantly higher biomass and grain yield compared to the other two. Field validation results show that the location-specific advisory (DGUC) resulted in about 8-17% grain yield increase compared to the standard and local checks. Biomass yield of plots that received the DGUC advisory showed 8% (1 t ha-1 increase compared to the local check). This indicated location-specific fertilizer rate advisory boosted not only grain yield but also biomass yield, which is one of the most valuable products for feeding livestock in Ethiopia. In addition, thousand seed weight and plant vigor were higher with site-specific fertilizer rate compared with local fertilizer rates. This is an important achievement demonstrating the value of integrated data analytics to make date-based and knowledge-informed decision making. During the 2021/2022 season, an attempt will be made to develop and provide bundled advisories composed of onset of rains and planting date (extracted from EDACaP, Ethiopian Digital AgroClimate advisory Platform) and a weather surveillance system developed by different partners (EIAR, Alliance and CIMMYT). This report summarizes the details of activities associated with the DGUC undertaken in the 2020/2021 cropping season in Ethiopia. The report is organized into different sections, including: (1) background of the project, validation trial protocol development; (2) field trip to districts and kebeles for discussion and site selection; (3) training and planning workshop held on validation trial implementation, management, data collection and use of open data kit (ODK) for digital data collection; (4) field book preparation and customization of data forms on ODK; (5) fertilizer treatment set up for the target development group (DG); (6) barcoded identification card preparation for digital data collection; (7) validation trial inputs and research materials purchase and distribution; and (8) trial follow up and visit by Alliance (CIAT) and Digital Green team, and farmers’ field day to evaluate the three fertilizer treatment performances based on their observation; (9) validation trial data collection and submission to ONA using ODK tool; and (10) research results from the fertilizer validation trial data.